(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: The objective of our study was to assess the functional results of Ilizarov fixator for treating proximal tibial fractures. Methods: The design of our study was descriptive and we conducted this study in the department of Orthopedics Surgery Unit-I, PGMI/ AMC, Lahore General Hospital, Lahore from 14-5-2018 to 14-11-2018. In this study, 75 patients fulfilling inclusion criteria were selected. After informed consent demographic information like name, age, gender and address of each patient was noted. The surgery is performed under C-arm fluoroscopy. All the patients were followed clinically for 24 weeks. In each visit pain was assessed with Visual Analogue Sacale (VAS) and range of knee motion measured with a goniometer. Results: A total of 75 patients with mean age 39.25±10.84 years were included in our study. Majority (81.3%,n=61) were males. Mean value of body mass index was 25.04±4.04. Majority(40%,n=30) of the cases belonged to Schatzker type III. Mild pain according to VAS was noted in the 43(57/3%). Knee range of motion was 106±6.82 degree post operatively. Conclusion: The Ilizarov external fixator is an excellent method of treating Proximal tibial fractures. It results in good knee range of motion post operatively and with low pain.